Molecular Epidemiology and Drug Resistance of Mycobacterium tuberculosis Isolates from Ethiopian Pulmonary Tuberculosis Patients with and without Human Immunodeficiency Virus Infection - Bruchfeld, Judith (American Society for Microbiology, 2002)
We have analyzed the molecular epidemiology and drug resistance of 121 Mycobacterium tuberculosis isolates from consecutive patients with culture-positive pulmonary tuberculosis attending a university hospital outpatient department in Addis Ababa, Ethiopia. Restriction fragment length polymorphism analysis and spoligotyping were used to analyze the DNA fingerprinting patterns. Fifty-one (41.2%) of the isolates were found in 13 clusters with two or more identical DNA patterns. Two such clusters contained 49.0% of all clustered isolates. In a multivariate logistic regression model, human immunodeficiency virus (HIV)-positive serostatus was significantly associated with clustering of isolates for patients of both sexes (odds ratio [OR], 2.55; 95% confidence interval [CI], 1.17 to 5.80). There was a trend toward increased clustering of isolates from tuberculous women residing in Addis Ababa (OR, 2.10; 95% CI, 0.85 to 5.25). In total, 17 of 121 isolates (14.0%) were resistant to one or more of the antituberculosis drugs isoniazid (8.3%), streptomycin (7.4%), rifampin (2.5%), and ethambutol (1.7%). The high rate of drug-resistant isolates (29.6%) coincided with the peak prevalence of HIV infection (77.8%) in patients 35 to 44 years old. The majority (62.5%) of resistant isolates in this group were found within clusters. The simultaneous accumulation of certain bacterial clones in a patient population likely reflects recent transmission. Hence, we conclude that tuberculosis is commonly caused by recent infection with M. tuberculosis in HIV-positive Ethiopian patients. Furthermore, with the rapidly increasing prevalence of HIV infection in Ethiopia, the burden of tuberculosis, including drug-resistant tuberculosis, is likely to increase. Strengthening of classical tuberculosis control measures by promoting active case finding among HIV-positive adults with tuberculosis is warranted to reduce rates of transmission.